Tinkering the Teacher–Technology Nexus: The Case of Teacher- and Technology-Driven Personalisation - Rani Van Schoors; Jan Elen; Annelies Raes; Fien Depaepe (Education Sciences, 2023)
Teacher-driven personalisation can be challenging to facilitate, especially in large heterogeneous classes and during demanding courses. Because of the growing digitalisation, more possibilities arise towards technology-driven personalisation. Nonetheless, little is known about how teachers interact with or implement digital personalised learning (DPL) tools in the classroom. This study explores two research questions: (RQ1) what personalisation strategies are enacted by teachers while implementing a DPL-tool for programming? and (RQ2) how does the teacher–technology interaction take shape? A qualitative multiple case study was established, comprising four cases (two pairs of co-teachers and two teachers who teach individually) implementing a DPL-track for programming in first grade of secondary education (12-to-14-year-old students). Within-case and cross-case analyses of interviews and observations revealed that, although the technology-driven personalisation remained unchanged over the cases, teachers used different personalisation strategies while enacting the DPL-track. Subsequently, various forms of the teacher–technology relationship were observed. Based on the findings, (1) a teacher–technology interaction continuum and (2) a new concept, i.e., ‘the teacher–technology nexus’, are presented as they can be of value for the elaboration of theory on the implementation of DPL-tools in real life classrooms.